(untitled) (Journal of Medicine, 2017)
Actinomycoses, a rare bacteriological illness whichis primarily involved in cervico-facial infections in susceptible populations. Thoracic, abdominal, pulmonary and cardiac involvement are also reported but are exceedingly rare in incidence. So, high degree of suspicion is required for early detection and treatment.We confirmed 2 cases of Actinomycosis, in the period of January, 2014 to July, 2015 with variable presentation and different outcome. J MEDICINE January 2017; 18 (1) : 47-51